Online Formative Assessment in Higher STEM Education; A Systematic Literature Review - Mahanan, Mangai Solomon; Abdul Talib, Corrienna; Ibrahim, Nor Hasniza (Asian Journal of Assessment in Teaching and Learning, 2021)
Online formative assessment in higher education Science Technology Engineering and Mathematics (STEM) is gaining attention in recent years based on the increasing use of online learning. This study, aimed at critically reviewing studies on online formative assessment in Higher education STEM between 2011 to 2020. The study adopted a qualitative research design to analyze studies based on specific themes. 1402 articles were systematically searched through Scopus, web of science, and google scholar databases. However, only 12 studies were included in this study after satisfying the inclusion criteria. All data analyses were done using the Endnote X9 reference manager. The findings reveal that, evidence about online tools used, theories used in the learning and assessment process, the domain of learning outcome assessed, assessment of practical skills, and form of assessment used have been implicitly described. However, the online formative assessments have shown great potential of yielding immediate feedback. Therefore, future studies can engage in a more extensive study on areas such as online assessment tools for assessing practical skills and strategies that can enhance the effectiveness of online formative assessment which encompasses all domains of learning outcome within STEM higher education.